2018
DOI: 10.11604/pamj.2018.30.156.10517
|View full text |Cite
|
Sign up to set email alerts
|

Caractéristiques des accidents du travail et devenir des victimes: à propos de 133 cas déclarés auprès de la Caisse de Sécurité Sociale de Dakar (Sénégal)

Abstract: IntroductionLes accidents du travail (AT) ont des répercussions sur le système de sécurité social du pays, sur les victimes elles-mêmes ainsi que leurs proches. L’objectif de notre étude est de décrire les différentes caractéristiques des AT déclarés auprès de la Caisse de Sécurité Sociale (CSS) de Dakar et le devenir socio-professionnel des victimes.MéthodesEtude rétrospective et transversale sur une période de 5 ans, de 2002 à 2006. Ont été colligés 133 cas sur 9.308 AT déclarés à la CSS. Divers paramètres o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 19 publications
0
6
0
4
Order By: Relevance
“…Dia SA et al in 2018 in Senegal [7] reported 44% of accidents in the morning and 26.7% in the afternoon.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Dia SA et al in 2018 in Senegal [7] reported 44% of accidents in the morning and 26.7% in the afternoon.…”
Section: Discussionmentioning
confidence: 95%
“…Building materials were the main causative agents of injuries, with a high frequency with a high frequency of 67.5% [9]. Dia S.A et al in Senegal in 2018 [3] had reported that 30% of the vulnating agents involved were hand tools.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Introduction : L'objectif était d'étudier les aspects épidémiologiques, cliniques, et la prise en charge chirurgicale des fibromyomes utérins au service de gynécologie-obstétrique de l'hôpital national Ignace Deen du CHU de Conakry en 2022. Méthodologie: Il s'agissait d'une étude descriptive transversale, allant du 1er Mai au 30 octobre 2022 soit une période de six (6) mois. Ont été étudié les variables épidémiologiques, cliniques et la prise en charge.…”
Section: Résuméunclassified
“…In the agricultural industry, especially in Senegal, accidents involving ingestion of caustic are rare [11]. In fact, this is mainly because current regulations and procedures in the handling of crop protection products and fertilizers are carried out in closed circuits and by only trained personnel.…”
Section: Introductionmentioning
confidence: 99%